A Study on Advancing Strategy of Seismic Tremors Solution For Busan using Open API (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background/Objectives: Among the earthquake damage analysis systems developed so far, no system that could even respond from the perspective of managers in the event of a disaster.Methods/Statistical analysis: It was intended to ensure the convenience of managers by adding additional functions to the type of seismic damage analysis system. The existing system predicted and calculated the damage caused by the earthquake. In this paper, we present a way to help respond quickly after an earthquake by using Open API, etc. It includes functions that are already being implemented, as well as those that are being researched and developed.Findings: The existing seismic damage analysis system mostly calculates building damage caused by earthquakes, evaluates the amount of damage based on those figures, and produces figures related to refugees. But when an actual earthquake occurs, there is not much that managers can do right away with the system. This paper presents a strategic improvement plan by adding four additional functions to overcome the shortcomings of the existing system. This improvement plan is based on 3D Geographic Information System (GIS) and was intended to add Earthquake Excellence History, Vulnerable Groups Concentrated Area Information, Standard Operating Procedures, and Real-Time Evaluation Route. Earthquake Accuracy History function allows an intuitive decision on past similar records to be made. Vulnerable Groups Concentrated Area Information function helps you make quick judgments about the situation in the region where you need help first and foremost. Standard Operating Procedures are built into the system so that non-skilled people can easily perform it. Real-Time Evacuation Route feature allows administrators to have a quick insight into the path of refugees.Improvements/Applications: The improvement plan with additional functions in the system for calculating the output related to damage can be further improved through further implementation.